The project Seeing is Believing unlocks USD 300,000 of financing for smallholder farmers in India - CGIAR Platform for Big Data in Agriculture (2021)
Evidence generated through the Seeing is Believing project, including a COVID-19 rapid response grant, helped unlock agricultural microcredit to farmers in Odisha, India. The rapid response grant allowed for de-risking of our partner Dvara E-Registry's "KhetScore" model, which uses georeferenced smartphone images to review and monitor crop loan applications. After a successful test of this lending model, Dvara attracted financing from a large private sector bank, expanding its scale of financing for smallholder farmers to an estimated USD 300,000.